1997
DOI: 10.1093/bja/78.6.754
|View full text |Cite
|
Sign up to set email alerts
|

“Best” PEEP during one-lung ventilation

Abstract: Eight patients were studied under general anaesthesia for elective pulmonary lobectomy to see if intrinsic positive end-expired pressure (PEEPi) would appear or increase in the dependent lung during one-lung ventilation (OLV) or if application of external PEEP equal to individually measured PEEPi would produce better arterial oxygenation, haemodynamic state and oxygen delivery than either zero PEEP (ZEEP) or an external PEEP 5 cm H2O greater than PEEPi. Patients were non-obese, without obstructive airways dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 5 publications
1
36
1
3
Order By: Relevance
“…During OLCV with capnothorax, a variety of pathophysiologic changes occur which may interfere with the ability of ventilated lung to maintain its normal FRC. In one study, the peak and inspiratory airway pressures were significantly lower during two-lung ventilation than at any time during OLCV [5]. In the present study, there were significant differences between the peak airway pressure before and during OLCV at different IPP.…”
Section: Discussionsupporting
confidence: 43%
“…During OLCV with capnothorax, a variety of pathophysiologic changes occur which may interfere with the ability of ventilated lung to maintain its normal FRC. In one study, the peak and inspiratory airway pressures were significantly lower during two-lung ventilation than at any time during OLCV [5]. In the present study, there were significant differences between the peak airway pressure before and during OLCV at different IPP.…”
Section: Discussionsupporting
confidence: 43%
“…Hence, not only defl ation of the lung but also hyperinfl ation of the lung may accelerate recovery from neuromuscular blockade. It has been reported that the magnitude of autopositive end-expiratory pressure (auto-PEEP) is higher during OLV than during TLV [7,8,10,11]. Inomata et al [10] noted that airway resistance increased because of a decrease in the compliance of the dependent lung during OLV, while they found that auto-PEEP was most likely to exist when airway resistance was increased.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the magnitude of autopositive end-expiratory pressure (auto-PEEP) is higher during OLV than during TLV [7,8,10,11]. Inomata et al [10] noted that airway resistance increased because of a decrease in the compliance of the dependent lung during OLV, while they found that auto-PEEP was most likely to exist when airway resistance was increased. They also postulated that auto-PEEP tended to appear in the dependent lung during OLV, primarily because of high airway resistance from a relatively small tracheal tube for OLV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mild to moderate PEEP levels are sufficient to keep recruited alveoli open in healthy subjects without deterioration of hemodynamics or hypoxic pulmonary vasoconstriction [107,108]. An external PEEP of 5 cmH 2 O did not increase the total PEEP in patients during OLV [109].…”
Section: Alveolar Recruitment Maneuver and Peepmentioning
confidence: 99%